Integration of two pKPX-2-derived antibiotic resistance islands in the genome of an ESBL-producing Klebsiella pneumoniae ST3483 from Lebanon. (September 2019) - Bitar, Ibrahim; Moussa, Jennifer; Abboud, Edmond; Hrabak, Jaroslav; Tokajian, Sima
Abstract: Objectives: Contamination of fresh water with clinically important Gram-negative bacteria in Lebanon is being investigated in-depth, especially with evidence of dissemination into clinical settings. This study aimed to report the draft genome sequence of a Klebsiella pneumoniae strain with an integrated plasmid segment harbouring two antibiotic resistance islands (ARI). It is believed that this is the first report of plasmid antibiotic resistance islands integration in the genome of K. pneumoniae . Methods: Whole genome sequencing of the isolate was performed using Sequel platform. The genome was assembled using HGAP4. Analysis was conducted by uploading the sequence to the online databases from the Center for Genomic Epidemiology. Results: The strain had a newly assigned ST 3483 with a genome size of 5385844 bp. The investigation of the antibiotic resistance islands suggested integration of two DNA segments from a previously identified IncFIA plasmid. The results revealed that the integration could have been accomplished either as a single-step integration event, with the two segments being integrated as a whole transposon mediated by the flanking IS 26, or through two separate integration events involving the two segments, but independently. Conclusion: The sequenced genome revealed interesting aspects related to antibiotic resistance dissemination. The ARI are more stable in the genome and the chance of losing it is less probable, with the possibility of the described transposon to re-integrate in other plasmids, facilitating the dissemination of such resistance determinants.